Effect of bioaugmentation on gas production and microbial community during anaerobic digestion in a low-temperature fixed-bed reactor - Wang, Yunlong; An, Xiaoya; Wang, Jian; Jiang, Xinbo; Li, Xue; Yin, Jiamin; Wang, Weidong; Piao, Jin; Zhao, Hongyan; Cui, Zongjun (Frontiers in Microbiology, 2024)
We investigated the effects of different concentrations of exogenous Methanomicrobium (10%, 20%, 30%) and different volumes of carbon fiber carriers (0%, 10%, 20%) on gas production and microbial communities to improve the performance of low-temperature anaerobic digestion systems. The results show that the addition of 30% exogenous microorganisms and a 10% volume of carbon fiber carrier led to the highest daily (128.15 ml/g VS) and cumulative (576.62 ml/g VS) methane production. This treatment effectively reduced the concentrations of COD and organic acid, in addition to stabilizing the pH of the system. High-throughput sequencing analysis revealed that the dominant bacteria under these conditions were Acidobacteria and Firmicutes and the dominant archaea were Candidatus_Udaeobacter and Methanobacterium. While the abundance of microorganisms that metabolize organic acids was reduced, the functional abundance of hydrogenophilic methanogenic microorganisms was increased. Therefore, the synergistic effect of Methanomicrobium bioaugmentation with carbon fiber carriers can significantly improve the performance and efficiency of low-temperature anaerobic fermentation systems.